Anagram Game to Enhance Students’ Vocabulary Mastery - Wardah Mutiah Nasution; Yusni Sinaga (English Education : English Journal for Teaching and Learning, 2020)
This research is focused on the effect of Anagram Game on the Students’ Vocabulary Mastery at VII Grade MTs N 2 Padangsidimpuan. This research aims to know the suitable and effective technique in teaching vocabulary. The research was an experimental research that uses one group pre-test and post- test design consist of 39 students in experimental class and 39 students in control class. The data were collected from students’ vocabulary test in the experimental class and control class. The result of this research have found from the t-test, which is tcount was higher than ttable (3.921.666). It was concluded that there was a significant effect of anagram game on the students’ vocabulary mastery. It means that the alternative hypothesis was accepted which indicates that anagram technique was significantly effective in teaching vocabulary. Additionally, anagram is a good vocabulary learning technique. It is an interesting game for learners. Thus, it is strongly suggested that teachers apply this technique to help enrich students’ vocabulary.